(untitled) (Revista Rupturas, 2015)
“Capital in the twenty-first century” is a book whose author is the French economist Thomas Piketty. It offers a wide research on the issue of inequality, mostly in the richest countries of contemporaneous capitalism. This work is based on very rich historical and empirical information, which in case of some countries, has extended within several centuries. From a theoretical point of view, this work has several problems, not just because its concept of capital is unsatisfactory, but because it formulates some “laws of capitalism”, that in fact are no more than countable relations or mere tautologies. But, in any case, Piketty gathers a lot of very useful empirical information, which is elaborated with care and rigor, and has fed a very important debate all over the world as well. At the same time, this book suggests some tendencies of the developing of the capitalism, and even thought the author doesn’t analyze them, or just try them in a superficial way, all of that generates new and very interesting possibilities for future research.